Microbial Mats in Silicilastic Depositional Systems Through Time 2012
DOI: 10.2110/sepmsp.101.075
|View full text |Cite
|
Sign up to set email alerts
|

Witwatersrand Metallogenesis: The Case for (Modified) Syngenesis

Abstract: The Witwatersrand (WWR) ores contain more gold than could have been derived in particulate form by erosion from any conceivable type of source area as proposed by the modified placer hypothesis. In contrast to this, syngenesis goes further to explain a host of observations from those Late Archean Au-U ores. Although recycling, placer processes, and processes of hydrothermal (diagenetic/authigenic) mobilization all contributed, syngenesis was a major factor contributing to ore genesis in this huge metallogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Geochemical modelling has shown that gold solubility in ancient waterbodies was much higher than today and that gold likely occurred as Au(I)-sulfide complexes (Heinrich, 2015). Different authors have suggested different precipitation mechanisms for these Au-complexes, including: i) adsorption (Mossman et al, 2008); ii) oxidative precipitation triggered by the release of oxygen on the surface of the microbial mats resulting from oxygenic photosynthesis (Frimmel, 2014;Frimmel and Hennigh, 2015); iii) precipitation via reduction by organic hydrocarbons (Heinrich, 2015); and iv) reductive precipitation as a result of bacterial activities (Horscroft et al, 2012). A laboratory study by Lengke et al (2006) has shown that the cyanobacterium Plectonema boryanum can withstand high concentrations of mobile Au-complexes and has the ability to biomineralize them to metallic nano-and micro-phase gold.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Geochemical modelling has shown that gold solubility in ancient waterbodies was much higher than today and that gold likely occurred as Au(I)-sulfide complexes (Heinrich, 2015). Different authors have suggested different precipitation mechanisms for these Au-complexes, including: i) adsorption (Mossman et al, 2008); ii) oxidative precipitation triggered by the release of oxygen on the surface of the microbial mats resulting from oxygenic photosynthesis (Frimmel, 2014;Frimmel and Hennigh, 2015); iii) precipitation via reduction by organic hydrocarbons (Heinrich, 2015); and iv) reductive precipitation as a result of bacterial activities (Horscroft et al, 2012). A laboratory study by Lengke et al (2006) has shown that the cyanobacterium Plectonema boryanum can withstand high concentrations of mobile Au-complexes and has the ability to biomineralize them to metallic nano-and micro-phase gold.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Evidence for gold enrichment during sedimentation, from a slightly older source exposed in the eroding hinterland of the basin, seems to be winning in the debate, and modified placer proponents are claiming victory 12,13 . While the debate has centred on the timing of gold introduction (see Supplementary Methods), the possibility and extent of syngenetic chemical transport of gold in surface water has received little attention 5,14 , despite clear observations that many pyrite concretions precipitated chemically 10,11,15 and delicate films of gold are coating vertical carbon fibres of wellpreserved former bacterial mats 5,9,14 . These textures suggest lowtemperature chemical precipitation in a mature regolith or in a quiescent lake, rather than mechanical accumulation in a fast-flowing river environment that is typical for modern placer deposits 5 .…”
mentioning
confidence: 99%
“…Gold may have been adsorbed into living cells 5,9 or was precipitated through abiotic reduction by organic carbon or hydrocarbons (represented by CH 4 ), as the third driver labelled 'life' in Fig. 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the likelihood of acidic conditions in rain and groundwater, enhanced by sulphur-rich volcanism, could also account for the high weathering and alteration indices which they reported. The action of acidic water on freshly ground glacial material could have enabled the dissolution and mobility of gold, which enhanced the grade of gold reefs, as proposed by Horscroft et al (2012) and Heinrich, (2015).…”
Section: Sediment Transport By Water or Ice?mentioning
confidence: 93%